Comparison of Circulating Tumour Cells and Circulating Cell-Free Epstein-Barr Virus DNA in Patients with Nasopharyngeal Carcinoma Undergoing Radiotherapy - Jess Honganh Vo (Nature Portfolio, 2016)
Abstract Quantification of Epstein-Barr virus (EBV) cell-free DNA (cfDNA) is commonly used in clinical settings as a circulating biomarker in nasopharyngeal carcinoma (NPC), but there has been no comparison with circulating tumour cells (CTCs). Our study aims to compare the performance of CTC enumeration against EBV cfDNA quantitation through digital PCR (dPCR) and quantitative PCR. 74 plasma samples from 46 NPC patients at baseline and one month after radiotherapy with or without concurrent chemotherapy were analysed. CTCs were captured by microsieve technology and enumerated, while three different methods of EBV cfDNA quantification were applied, including an in-house qPCR assay for BamHI-W fragment, a CE-IVD qPCR assay (Sentosa ®) and a dPCR (Clarity™) assay for Epstein-Barr nuclear antigen 1 (EBNA1). EBV cfDNA quantitation by all workflows showed stronger correlation with clinical stage, radiological response and overall survival in comparison with CTC enumeration. The highest detection rate of EBV cfDNA in pre-treatment samples was seen with the BamHI-W qPCR assay (89%), followed by EBNA1-dPCR (85%) and EBNA1-qPCR (67%) assays. Overall, we show that EBV cfDNA outperforms CTC enumeration in correlation with clinical outcomes of NPC patients undergoing treatment. Techniques such as dPCR and target selection of BamHI-W may improve sensitivity for EBV cfDNA detection.